فاعلية تصميم تعليمي قائم على انموذج ديفز في تنمية مهارات تلامذة المرحلة الابتدائية بمادة الاشغال اليدوية (Journal of the College of Basic Education, 2024)
The research aims to identify " The effectiveness of according to an instructional design based on the Davis model in developing the skills of primary school students with handicrafts " by verifying the following research hypotheses :1- There are no statistically significant differences at the level of significance (0.05) between the mean scores of the students of the experimental group andthe average scores of the students of the control group in the cognitive achievement test of the subject of art education, postgraduate.2- There are no statistically significant differences at the significance level (0.05) between the mean scores of the experimental group students and the mean scores of the control group students in the post-skills performance test.The researcher used the experimental design with the post test, and the current research community consisted of sixth grade students / Abu Ghraib Mixed Primary School / First Karkh Education Directorate / in Baghdad Governorate / for the academic year (2022-2023 AD), and the size of the community reached (720) male and female students, while the sample of the current research consists of (30) male and female students for each group, the experimental and the control, and the researcher chose the research sample by the intentional method, and the number of students in the sixth grade reached (106) male and female students, distributed over three classes, then the researcher chose two classes Of them, in a random way, Division (A) of (35) male and female students was tested to represent the control group, while Division (C) of (34) was tested to represent the experimental group, and the total number of the two classes was (69), and the researcher excluded (9) from The students of the control and experimental groups (3) dropped out, (4) failed, and (2) were transferred to another school, and the researcher used the (ssps) program to reach the results, and the results of the current research show the superiority of the students of the experimental group that studied with handicrafts subject according to the educational unit on the students of the control group who studied the same subject according to the usual way.